Developing Students’ Entrepreneurship Competencies through Problem and Project Based Learning Model - Putriyani S; Suarti Djafar; Sugian Nurwijaya (Edumaspul: Jurnal Pendidikan, 2023)
Indonesia often faces the problem of a lack of job opportunities which results in high unemployment and fewer opportunities to find work for school graduates. Therefore, teacher innovation is needed in learning to foster student competencies such as creativity, critical thinking, problem-solving, collaboration, communication and so on, in which these competencies can be summarized as entrepreneurship competencies. Entrepreneurship competencies needs to be cultivated in every student to form an entrepreneurial spirit, so that they can realize economic development and open their own jobs. To build entrepreneurship competencies through internalization in life, learning in schools requires a comprehensive study of the potential of the learning model used by teachers in learning mathematics. Student-centred learning models such as Problem-based Learning and Project-based Learning indirectly build and instill entrepreneurship competencies in students, including creativity, problem-solving, critical thinking, collaboration, communication, and independence.